A cross-sectional study on the assessment of impact of demonetization of Rs.500 and Rs.1000 currency notes on the socio-economic and health status of the people residing in an urban area of Kanchipuram district - Hariharan, S.; Krishnakumar, J.; Stephen, T. (International Journal Of Community Medicine And Public Health, 2018)
Background: The Government of India took the historic move of demonetising Rs.500 and Rs.1000 currency notes of Mahatma Gandhi Series from the midnight of 8th November 2016, following which these high value currency notes ceased to be a legal tender.It was a radical move by the Government which had an impact on the socio-economic and health status of the people. The study was conducted to assess the impact of demonetization move on the socio-economic and health status of the people residing in Anakaputhur area of Kanchipuram district. Methods: A cross-sectional, questionnaire based study was conducted on people residing at Anakaputhur area of Kanchipuram district. A sample size of 272 people was obtained using convenient sampling method. The study was conducted from 1.3.2017 to 1.4.2017. Data entry was done in Microsoft Excel and analysis was carried out in SPSS 22 software. Descriptive analysis was done. Results: Of the total study population of 272 people, 157 were females and 115 were males. Majority of the participants (58.1%) had used only cash for making their payments. Majority of participants (60%) responded that they were satisfied with the demonetization move. Majority of participants (67%) responded that the demonetization move would lead to overall economic development of our country. Conclusions: Even though the Government’s intention behind demonetization was good, the process by which the move was implemented could have been better. Government could have taken proper anticipatory measures to prevent cash crunch.